مناهج تعليم العربيّة بالجزائر بين البناء وتحدّيات العولمة - مقاربة تقويميّة لمناهج المرحلة المتوسّطة - زريق إبتسام (جامعة الوادي - University of Eloued, 2025)
تهدف هذه الورقة البحثيّة إلى رصد أهمّ الإصلاحات التّي شهدها النّظام التّعليمي في الآونة الأخيرة الشّاملة للمستويين المعرفي والمنهجي، والهدف من هذه الإصلاحات، هو تطوير المنظومة التّربوية، ومسايرة التطوّر والحداثة في الميدان التّعليمي التعلّمي الذّي يعدّ العامل الرّئيس في تّقدم الدّول وتطوّرها، وفي ظلّ هذه الإصلاحات فإنّ أهمّ ما يمكن الوقوف عنده المنهاج المستحدث الذّي من شأنه أن يؤثّر إيجابا أو سلبا على عمليّتي التّعليم والتّعلم، لذا سنسعى من خلال محطّات هذا البحث إلى الحديث عن تطوّر منهاج اللّغة العربيّة في المرحلة المتوسّطة، وبيان أثره في العمليّة التّعليميّة التّعلميّة، بالوقوف عند أهمّ التّغييرات الطّارئة عليه، من جهة، والكشف عن إيجابيّاته وسلبيّاته من جهة أخرى. لتثمر نتائج البحث عن الآتي: عرفت المناهج في بلادنا مراحل عديدة؛ كلّ مرحلة منها تكمّل سابقتها، وتحاول منح العالميّة للمناهج المدرسيّة، وذلك من خلال إعادة النّظر في مكوّنات المنهاج، من محتويات وطرائق وآلياتٍ للتّقويم، وكلّ ذلك من أجل تكوين متعلّم قادر على التّفاعل مع أفراد المجتمع الذّي يعيش فيه. . This research paper aims to monitor the most important reforms that the educational system has witnessed in recent times. Which included the cognitive and methodological levels, and the aim of such reforms is: to develop the educational system, and keep going with development and modernity in the educational and learning field, which is the main factor in the progress and development of countries. In light of these reforms, the most important thing that can be considered is the curriculum, which was affected by reform that would affect positively or negatively on teaching and learning. Therefore, we will seek through the stations of this research to talk about the role of the development of the Arabic language curriculum in the intermediate stage, and to indicate its impact on the process. The educational process, by examining the most important changes in it, on the one hand, and revealing its positives and negatives, on the other hand. so the results of the research appear on the following, the curricula have known many stages, each of which is based on the ruins of the previous one, and tries to grant universality to the school curricula, by reconsidering the components of the curriculum, including contents, methods and mechanisms for evaluation, and all this in order to form a learner who is able to interact with members of the community which he lives.
Arabic Teaching Curricula In Algeria Between Construction And The Challenges Of Globalization – An Evaluative Approach Of Middle School Curricula
مقال .مجلة علوم اللغة العربية وآدابها. مج 17. ع 02
Keywords: منهاج اللّغة العربيّة؛ بناء المنهاج؛ تحدّيات العولمة؛ تعليم؛ الجزائر؛ مرحلة متوسّطة .; Arabic language curriculum; building the curriculum; challenges of globalization; Education; Algeria; middle school